Design-property decision-making in polymer lattices when controlling for printed mass - Clares, A. P.; Manogharan, G.; Thomas, L.; Krzeminski, D. (Sports Engineering, 2023)
This study aims to demonstrate the ability of additive manufacturing to enhance the performance of polymer lattices in sporting equipment by establishing a systematic workflow for rapid design-fabrication-performance evaluation. The investigation develops a framework to enable optimal selection of lattice design and performance variables such as printed mass and compressive modulus. The objectives were to: (i) define a comprehensive workflow to evaluate lattices using a polymer laser powder bed process, namely—selective laser sintering, (ii) investigate the printability and compression performance of commonly designed selective laser sintering lattices for sporting equipment, and (iii) understand the design-property relationships when controlling for printed mass (via digital lattice volume). Sixteen 50 × 50 × 30 mm specimens of varying lattice type, strut/sheet thicknesses and cell sizes were printed (NTotal = 92, n = 3 per design) using two different elastomeric and rigid materials to achieve four pre-set mass groups. Quasi-static compression testing revealed that modulus, stress at 30% strain, and energy capacity show broad ranges of 2.4-7.0 × for equivalent printed mass and strut/sheet thicknesses. Design-property relationships were validated across multiple pre-set mass ranges which has not been reported. This study showed that compression properties of SLS lattices across soft and rigid materials can be selectively tuned while maintaining mass targets. Findings could be leveraged in designing and fabricating lattices for superior performance of sports equipment, such as co-design of lattice configuration and material selection-processing conditions).